2018
DOI: 10.1111/jam.13768
|View full text |Cite
|
Sign up to set email alerts
|

High diversity and variability in the bacterial microbiota of the coffee berry borer (Coleoptera: Curculionidae), with emphasis onWolbachia

Abstract: This study demonstrates that stage of development and origin of samples affected the structure and function of the CBB's bacterial communities. This is the first attempt to predict functional significance of the CBB microbiota in nutrition, reproduction and defence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 102 publications
(105 reference statements)
3
18
2
1
Order By: Relevance
“…In B. dorsalis , the bacterial communities dominated by Proteobacteria and Firmicutes differed at different developmental stages (Andongma et al, 2015). A recent report on microbial profile of another beetle, H. hampei whose microbiota is highly diverse and variable displays a high degree of similarity in bacterial structure and composition with our study insect (Mariño et al, 2018). On contrary, the bacterial community structure in life stages and two sexes of the Chinese white pine beetle, Dendroctonus armandi exhibited no significant differences (Hu et al, 2013).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…In B. dorsalis , the bacterial communities dominated by Proteobacteria and Firmicutes differed at different developmental stages (Andongma et al, 2015). A recent report on microbial profile of another beetle, H. hampei whose microbiota is highly diverse and variable displays a high degree of similarity in bacterial structure and composition with our study insect (Mariño et al, 2018). On contrary, the bacterial community structure in life stages and two sexes of the Chinese white pine beetle, Dendroctonus armandi exhibited no significant differences (Hu et al, 2013).…”
Section: Discussionsupporting
confidence: 60%
“…Overall, diversity estimation revealed higher bacterial species richness and community diversity in the eggs followed by adult female and male and their respective reproductive organs and the lowest in the pupal and larval stages, respectively (Figure 1 and Table 1). A number of factors have been identified to affect the structure and composition of microbiota including host genetics, age, sex, diet, and geography (Adams et al, 2010; Elijah Powell et al, 2018; Mariño et al, 2018). The higher number of OTUs found in the eggs is comparable with the microbial diversity of Spodoptera littoralis , which might have caused due to exposure to a wide range of environmental microorganisms (Meng et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S30, S75 only had ndmE (heads) (Tables 1, 2 and Figure 3). Mariño et al (2018) reported 392 bacterial genera in the microbiome of eggs and whole adult female coffee berry borers, with a preponderance of Pseudomonas and Pantoea. Pseudomonas spp.…”
Section: Pseudomonas and Delftia In The Coffee Berry Borermentioning
confidence: 99%
“…For example, beneficial bacteria that are only necessary during a single life stage, such as the facultative gut bacteria of larval mosquitos ( Aedes aegypti ) (Linnaeus, Diptera: Culicidae), are ingested by their hosts through feeding in the surrounding environment ( Coon et al 2016 , 2017 , 2020). Shared adult and larval habitat can act as multigenerational bacterial reservoirs for horizontal transmission, as in the coffee berry borer Hypothenemus hampei (Ferrari, Coleoptera: Curculionidae) ( Mariño et al 2018 ) and its facultative bacteria. The acquisition of symbiotic facultative bacteria through food is demonstrated in vinegar flies as well, through the defecation and regurgitation of hosts into food sources and subsequent re-acquisition ( Pais et al 2018 , Storelli et al 2018 ).…”
Section: Mechanisms Of Transmissionmentioning
confidence: 99%